PENGARUH CURRENT RATIO, DEBT RATIO, DAN RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN SEKTOR KESEHATAN - Rahayu, Ajeng Kurnia; Nurdiwati, Diah; Kurniawan, Andy (Universitas Nusantara PGRI Kediri, 2022)
This research was conducted as a way in the process of knowing the effect of the current ratio, debt equity ratio, and return on equity of a firm's value both in partial and simultaneous terms on health sector companies listed on the IDX. With multiple linear regression method with SPSS software version 23. This result shows that the current ratio and debt equity ratio partially have no significant effect on firm value. However, the return on equity ratio in the partial form has a significant effect on a firm's value. However, the current ratio, current ratio, debt equity ratio and return on equity have a simultaneous effect on firm value in health sector companies listed on the Indonesia Stock Exchange in 2018-2021. Previous research was conducted on pharmaceutical sector companies listed on the IDX for the period 2013-2017, while the business in this study was carried out through health sector companies listed on the IDX with different years, 2018-2021.